1985
DOI: 10.1111/j.1432-1033.1985.tb08921.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete amino acid sequence of bovine plasminogen

Abstract: The amino acid sequence of the single polypeptide chain of bovine plasminogen (786 residues, M , 88092) was determined. Cleavage with CNBr yielded 13 fragments of which six originated from cleavage sites different from human plasminogen. Digestion with elastase gave three major fragments: kringles (1 + 2 + 3) and kringle 4, both with intact lysine binding sites, and mini-plasminogen. Subfragmentation was achieved mainly with 2-(2-nitrophenylsulfenyl)-3-methyl-3'-bromoindolenine (BNPS-skatole), Staphylococcus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 30 publications
2
36
0
2
Order By: Relevance
“…Amino acid sequence analysis revealed that bovine and porcine plasminogen, like the human molecule, both contain two glycosylation sites. The N-glycosidic linkage involving AsnZS9 of BPG and PPG was localized in the corresponding position of kringle 3 ; however, the 0-linked carbohydrate attachment site was shifted to Ser339 in the bovine and to Thr249 in the porcine protein [12,131. In addition, a varying degree of N-glycosylation was found to be responsible for differences in total carbohydrate between the three species investigated in the present study [9].…”
mentioning
confidence: 99%
“…Amino acid sequence analysis revealed that bovine and porcine plasminogen, like the human molecule, both contain two glycosylation sites. The N-glycosidic linkage involving AsnZS9 of BPG and PPG was localized in the corresponding position of kringle 3 ; however, the 0-linked carbohydrate attachment site was shifted to Ser339 in the bovine and to Thr249 in the porcine protein [12,131. In addition, a varying degree of N-glycosylation was found to be responsible for differences in total carbohydrate between the three species investigated in the present study [9].…”
mentioning
confidence: 99%
“…Anilinothiazolinone derivatives were converted to the corresponding phenylthiohydantoins by an automated conversion system and identified by HPLC [27]. …”
Section: Sequence Analysismentioning
confidence: 99%
“…In blood, Pg is involved in the Iysis of fibrin clot. Blood vessel endothelium synthesizes the tissue Pg-activator (t-PA), a serine proteinase, which is able, by splitting the single peptide bond 557-558, to convert Pg into plasmin, another serine proteinase, consisting of a heavy and a Iight chain linked by 2 disulfide bridges (Schaller et al, 1985). A small proportion of Pg is transferred to milk in which both Pg and plasmin are found in a ratio of ca.…”
Section: Lactoferrinmentioning
confidence: 99%
“…Plasmin (EG 3.4.21.7) Bovine plasminogen (Pg) is a single-chain blood serum protein composed of 786 amino acid residues with a number of disulfide bridges and 2 carbohydrate moieties (Schaller et al, 1985). In blood, Pg is involved in the Iysis of fibrin clot.…”
Section: Lactoferrinmentioning
confidence: 99%